Quality of Integrated Information System Blueprint based on Enterprise Architecture Scorecard - Purna Kurniawan, Ady (International Journal of Engineering and Technology, 2019)
Enterprise architecture development of information system in an organisation is very important for running its bussiness process. This research uses EAP (Enterprise Architecture Planning) metodology for planning enterprise architecture, and E2AF (Extended Enterprise Architecture Framework) for mapping and organizing the results of the design is already done. Then the resulf of its mapping is measured by a questionaire from Enterprise Architecture Scorecard by colecting EAPâ€™s documentations. The result of mapping between EAP into E2AF shows that EAP fillfull 3 (three) levels and 1 (one) level only for information system aspect in E2AF.The assessment process using EA Scorecard shows the percentage value of 71.875% of the documentation on mapping of EAP steps into E2AF. Overall, this research produced a blueprint for the development of an integrated information system in accordance with the business processes of Tri Dharma of University in UMS.Â Â